(untitled) (World Bulletin of Public Health, 2024)
The article presents generalized data on the problem of heart rhythm disturbances in the fetus and newborns. The etiology, structure, classification, diagnostic methods and electrocardiographic criteria of some arrhythmias, therapeutic tactics in identifying fetal and neonatal arrhythmias are described.